2003
DOI: 10.1046/j.1365-2400.2003.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mortality of wild and released reared 0‐group turbot, Scophthalmus maximus, on an exposed beach (Ría de Vigo, NW Spain) and a study of the population dynamics and ecology of the natural population

Abstract: Marked reared turbot, Scophthalmus maximus (L.) (594) were released onto an exposed beach nursery ground together with marked wild fish (438) of approximately the same size (4–6 cm TL) and were sampled at intervals for 38 days. A consistent ratio of marked wild: unmarked wild indicated that marking did not increase mortality. The wild 0‐group turbot population size was estimated at 1540 at the time of release, indicating that hatchery‐reared individuals could theoretically make a significant contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…This result was in agreement with results obtained elsewhere for turbot (Iglesias et al, 2003) and Japanese flounder (Paralichthys olivaceus) (Furuta et al, 1997). Conditioning fish to their new environment before release was shown to limit post-release mortality , as was suggested by several authors (e.g., Kellison et al, 2000;Fairchild and Howell, 2004).…”
Section: Introductionsupporting
confidence: 92%
“…This result was in agreement with results obtained elsewhere for turbot (Iglesias et al, 2003) and Japanese flounder (Paralichthys olivaceus) (Furuta et al, 1997). Conditioning fish to their new environment before release was shown to limit post-release mortality , as was suggested by several authors (e.g., Kellison et al, 2000;Fairchild and Howell, 2004).…”
Section: Introductionsupporting
confidence: 92%
“…To our knowledge, large-scale stock enhancement programs have not been performed yet for any of the cultivated European flatfish species. In turbot, some experimental stock enhancement exercises have been conducted in Spain, Denmark, Belgium and Norway (Iglesias and Rodríguez-Ojea 1994;Coughlan et al 1998;Støttrup et al 2002;Iglesias et al 2003;Nielsen et al 2004;Støttrup 2007, 2008). Some small-scale releases of hatchery-reared turbot have been also reported, aimed to enhance stocks available for recreational fishing; Paulsen and Støttrup (2004) referred to more than 800,000 reared juvenile turbot released between 1990 and 2002 in Danish waters.…”
Section: Performance Of Domesticated Flatfish In the Wildmentioning
confidence: 99%
“…or 1? year class), which were released in shallow coastline habitats where hatcheryreared turbot generally exhibited highest (Iglesias et al 2003) or similar (Støttrup et al 2002) mortality compared to wild turbot of the same age. Although differences in prey and feeding behavior between wild and reared turbots occurred (Ellis et al 2002), domestic juveniles seemed to be able to adapt to natural diet within a few weeks and to exhibit similar growth rates to wild animals (Iglesias and Rodríguez-Ojea 1994;Paulsen and Støttrup 2004).…”
Section: Performance Of Domesticated Flatfish In the Wildmentioning
confidence: 99%
“…For example, considerable empirical evidence has shown that decreases in the genetic variability of hatchery fish broods can adversely affect their fitness. Typical problems include low survival rates at one or more life stages, low reproductive success (e.g., fewer gametes, gametes of poor quality, lack of spawning activity), slow growth, poor physiological adaptation, abnormal mechanical function (e.g., swimming, feeding), developmental alterations, and morphological abnormalities (see Iglesias et al, 2003;Asahida et al, 2004).…”
Section: Decreases In Fitnessmentioning
confidence: 99%